Statistical analysis of the new catalogue of CP stars - Ghazaryan, S.; Alecian, G.; Hakobyan, A. A.
This talk is devoted to the statistical analysis of the new catalogue of Chemically Peculiar stars compiled from papers, where chemical abundances of those stars were given. The catalogue contains chemical abundances and physical parameters of 428 stars based on high- resolution spectroscopy data. Spearman's rank correlation test was applied for 416 CP (108 HgMn, 188 ApBp and 120 AmFm) stars and the correlation between chemical abundances and different physical parameters (effective temperature, surface gravity and rotational velocity) was checked. From dozens interesting cases we secluded four cases: the Mn peculiarities in HgMn stars, the Ca correlation with respect to effective temperature in AmFm stars, the case of helium and iron in ApBp stars. We applied also Anderson-Darling (AD) test on ApBp stars to check if multiplicity is a determinant parameter for abundance peculiarities.
Keywords: Stars